The cGAS-STING pathway in ischemia-reperfusion injury in acute cerebral infarction: a new therapeutic opportunities? - Jun Hu; Mengxiang Tian (Frontiers in Neurology)
The innate immune response is the body's first line of defense against external pathogens and endogenous damage signals. The cGAS-STING pathway is a crucial component of the innate immune response, playing a key role in initiating antiviral and anti-infective immune responses by recognizing cytosolic DNA. Acute cerebral infarction is one of the leading causes of death and disability worldwide, with the primary treatment approach being the restoration of blood flow to ischemic brain tissue. However, reperfusion injury remains a significant challenge during treatment. The overactivation of the cGAS-STING pathway and its association with ischemia-reperfusion injury have been confirmed in numerous studies. This article will systematically elucidate the mechanisms of the cGAS-STING pathway, its role in ischemia-reperfusion injury in acute cerebral infarction, the current research status of cGAS-STING inhibitors, and the application of nanomaterials in this context, evaluating the therapeutic potential of this pathway.